Fluid dynamics : theory, computation, and numerical simulation - Pozrikidis, C. 1958- (Springer, 2016)
This is the first book that extends the classical field of fluid dynamics into the realm of scientific computing. It is both comprehensive and accessible to the beginner. The book is supplemented by a free web-based software library, FDLIB, and MatLab.- Resumé vydavatel